RE: Are Cross-Sectional Imaging Modalities Enough for Sarcopenia Assessment? - Rasim Eren Cankurtaran,; Yasin Celal Güneş,; Emre Dirican,; Oktay Algın,; Damla Cankurtaran,; Öykü Tayfur Yürekli, (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Cankurtaran RE, Güneş YC, Dirican E, Algın O, Cankurtaran D, Tayfur Yürekli Ö. RE: Are cross-sectional imaging modalities enough for sarcopenia assessment? Turk J Gastroenterol. 2024;35(1):75.